Islamic Moral Values ​​in Indonesian Cinema: A Hadith Reading of Ipar Adalah Maut - Della Rahmayani; Rahma Nurwahyuningsih; Yusna Kamila Firdausi; Fina Thazha Eka Sari; Jamilatul Dwi Aulia Khasanah (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study aims to analyze the moral values represented in the film Ipar Adalah Maut through the normative framework of the Hadith of the Prophet Muhammad, particularly those related to the concept of al-hamw (brother-in-law), the prohibition of approaching adultery, and the control of lustful desires. The film represents a contemporary popular cultural text that portrays moral tensions within family life as well as the boundaries of Islamic ethics. The narrative, which centers on a forbidden relationship between a husband and his sister-in-law, presents fundamental issues related to family ethics, moral responsibility, and violations of religious norms. Using a qualitative-descriptive method with a library research approach, the analysis is conducted by examining the content of key scenes, dialogues, and characters in the film, which are then systematically interpreted based on relevant hadith texts. The results of the study show that the film represents a serious deviation from Islamic family ethics, reflected in the violation of marital trust, the weakening of social boundaries with a sister-in-law, and the normalization of emotional closeness that ultimately leads to moral degradation. These findings affirm the relevance of the hadith al-hamw al-mawt as a preventive ethical warning regarding the dangers of uncontrolled relations with a sister-in-law. This research contributes to strengthening hadith as a normative ethical framework in the analysis of popular films, thereby bridging doctrinal hadith studies with contemporary cultural realities, while also emphasizing the potential of film as a reflective and educational medium in reinforcing Islamic family ethics amid the dynamics of modern society.